2022
DOI: 10.7759/cureus.27471
|View full text |Cite
|
Sign up to set email alerts
|

Role of Saliva as a Non-Invasive Diagnostic Method for Detection of COVID-19

Abstract: SARS coronavirus2 is the primary cause of new Coronavirus illness (COVID-19) (SARS-COV-2). Today, COVID-19 is a global epidemic. Coronavirus illness may be diagnosed using a variety of approaches. The gold standard is RT-PCR, which is used in all of these assays. Swabs from the nose, pharynx, or mouth are the most often used sampling methods for coronavirus detection. For COVID-19 testing, saliva may be utilized as an alternate sample. When compared to a nasopharyngeal swab, saliva samples have a number of adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 31 publications
(57 reference statements)
0
6
0
Order By: Relevance
“…Importantly, this positive salivary detection corroborated viral detection via nasopharyngeal swabs. 44 More recent studies confirm the detection of SARS-CoV-2 in saliva (Huang,Isho,35,(45)(46)(47). 35 Using paired samples of nasopharyngeal swab and saliva from 299 individuals, Salu et al reported a 67% positive agreement of the saliva samples with the nasopharyngeal swab.…”
Section: Oral Microenvironment: Bacterial Viral Pathogens and Host Fa...mentioning
confidence: 86%
See 2 more Smart Citations
“…Importantly, this positive salivary detection corroborated viral detection via nasopharyngeal swabs. 44 More recent studies confirm the detection of SARS-CoV-2 in saliva (Huang,Isho,35,(45)(46)(47). 35 Using paired samples of nasopharyngeal swab and saliva from 299 individuals, Salu et al reported a 67% positive agreement of the saliva samples with the nasopharyngeal swab.…”
Section: Oral Microenvironment: Bacterial Viral Pathogens and Host Fa...mentioning
confidence: 86%
“…45 Due to its accuracy and non-invasive nature, salivary coronavirus diagnostics replaced swabs from the nose, pharynx, and mouth as the preferred sampling method for SARS-CoV-2 detection. 46 Besides viral genome detection, rapid (minutes compared to hours for Reverse Transcription-quantitative Polymerase Chain Reaction) antigen-based assays were developed for Point-of-Care or athome testing. Marin et al detected seven (spike, nucleocapsid, membrane, replicase polyproteins 1ab (R1AB), R1A/R1AB, ORF3a, and ORF9b) out of 18 SARS-CoV-2 proteins in the saliva of COVID-19 subjects (n = 42).…”
Section: Oral Microenvironment: Bacterial Viral Pathogens and Host Fa...mentioning
confidence: 99%
See 1 more Smart Citation
“…A noninvasive method might be better for their overall experience, could reduce resistance toward testing and may lead to higher quality samples due to an effortless execution. Alternative noninvasive methods such as saliva swabs or collectors have already been proven to have a high concordance rate of 90% when compared to NPS 17 . However, this method requires special tubes or sponges for saliva collection, which can be expensive, difficult and time‐consuming for laboratory testing.…”
Section: Introductionmentioning
confidence: 99%
“…Alternative noninvasive methods such as saliva swabs or collectors have already been proven to have a high concordance rate of 90% when compared to NPS. 17 However, this method requires special tubes or sponges for saliva collection, which can be expensive, difficult and time-consuming for laboratory testing.…”
mentioning
confidence: 99%